Breaking the Ethnic Barrier in Mark 7:24-30: Implication for the Ghanaian Context - Alice Matilda Nsiah (Noyam Publishers, 2021)
The study aims at interpreting Mark 7:24-30 to establish whether Jesus was initially reluctant in helping a needy woman because she was non-Jewish, or the author was establishing the gradual breaking of ethnic and all other barriers to redefine the scope of Jesus’ ministry. The study uses African Biblical Hermeneutic theory of Gerald West that allows a dialogue between the text and the African context. It argues that the text may be interpreted as a covenant renewal discourse aimed at including Gentiles into the covenant family. The study concludes that unproductive ethnic and religious barriers may be broken for the common good of God’s family. It recommends the importance of mutual respect in dialogue in the face of diversities of opinions and perspectives.